PERAN GURU OLAHRAGA DALAM MENINGKATKAN SEMANGAT BELAJAR SISWA DI SDN. 097359 PONDOK BARU - Suyono; Adil Rosyadi Hasibuan; Nur Hasanah Ramdhani; Latifah Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Passion for learning is a crucial factor that students need to have during their learning process. This is reflected in the way students approach learning with great sincerity and perseverance, completing assignments well, actively participating in class, even being enthusiastic about additional assignments, and not easily feeling tired or discouraged. The level of student enthusiasm for learning can be influenced by the surrounding environment, which makes the role of teachers very important in maintaining and improving it, especially sports teachers. Qualitative descriptive research methods using literature studies and interviews, the results show that the role of sports teachers in increasing elementary school students' enthusiasm for learning has significant value. By creating a pleasant learning environment, improving cognitive and physical skills, forming character and values, and improving student health and well-being, PE teachers can have a major positive impact on student learning success.